¿Anarquistas, ambientalistas o revolucionarios? La conflictividad rural en Chalco. San Francisco Acuautla contra Zoquiapa, 1850-1868 - Tortolero Villaseñor, Alejandro (2009)
This essay analyzes material and cultural explanations of rural rebellions in Chalco, Mexico between 1760 and 1920. In that period, several social and economic changes took place which reveal the consolidation of the commercial hacienda against pueblos communal resources. This situation produced several agrarian conflicts; this paper analyses one of those conflicts: that of 1868. The study of that conflict discloses the composition of the rural movement in its anarchist and environmental dimensions. This paper argues that the pueblos defended their natural resources and consequently their way of life by using an ?environmentalist? discourse. Such a discourse was inserted at a crossroads of conflict and negotiation in Chalco.